(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the chemical composition, fermentative profile and fermentative losses of elephant grass (EG) silage with different levels of forage palm (FP) and cupuaçu seed cake (CSC). A completely randomized design (CRD) was adopted, in a 2x3+2 factorial scheme, with five replicates each, totaling 40 experimental mini silos, with storage for 50 days. Eight treatments were evaluated, one consisting only of EG, a pool containing 40% EG, 30% CSC and 30% FP, both mixtures at levels of 20, 40 and 60%. After opening, dry matter losses (DML), by gases (GL) and effluents (EL) were measured. Bromatological parameters and hydrogen potential (pH) were determined, organic acids and ammoniacal nitrogen were determined. Aerobic stability was determined by measuring the temperature at times 0, 12, 24, 48, 72 and 96 hours after opening the silos. For dry matter, there was a quadratic variation (P<0,05), where the pool and treatments with inclusion of 40 and 60% CSC obtained the lowest pH value (4,22). It was concluded that EG losses were minimized with the inclusion of 60% CSC, while the pool was intermediate, both in bromatological and fermentative terms.